Batik MSME acceptance model for appropriate technology on fabric laying tables and dye liquid containers in East Kalimantan, Indonesia (BIS Humanities and Social Science, 2026)
The creative industry as a strategic sector is not only complementary but also able to boost significantly the national economy. Craft is a sub-sector of the creative industry that has great opportunities to develop continuously due to its abundant natural resources as well as it is supported by creative and innovate human resources. Craft products such as handicrafts, traditional textiles and art objects have attracted interest from overseas markets. Batik crafts in East Kalimantan had also been developed into fashion products with the start of holding a lot of fashion shows, one of which uses batik as the material, so that batik in East Kalimantan had great potential. It was because Batik was not only apart from being included in the craft sub-sector but also included in the fashion sub-sector where both sub-sectors were included in the top three creative industry sub-sectors contributing to national GDP. One aspect that was able to be used as part of a business strategy is innovation. One of the innovations made to help batik work is a means of placing batik cloth when coloring using the dabbing technique. It is a table equipped with a hanging container for the dye liquid in order to make the batik maker easy use it because there is no risk of spilling onto the batik cloth as well as it is able to be moved according to the position of the batik maker since it has a rail on it. Based on the background, it was necessary to conduct research on the acceptance model of batik MSMEs towards appropriate technology on cloth placement tables and dye liquid containers. The methods used were validity test, reliability test, and Spearman rank correlation test. The result showed that the correlation between Perceived Usefulness and Actual System Use variables had a strong level of relationship because the value was 0.915 as well as Perceived Ease of Use with Actual System Use variables with a value of 0.850. In addition, the correlation value of both had a two-star mark so that the value was significant, or in other words, there was a positive and significant relationship between the Perceived Usefulness variable with the Actual System Use variable and also Perceived Ease of Use with the Actual System Use variable.